Development of ‘Truth or Dare’ Team Games Tournament-Based Biology Media for Teaching Digestive System in Senior High School - Aulia Andin Kinanti; Kartika Manalu (Universitas Labuhanbatu, 2025)
Background: Low student engagement and learning outcomes in biology, particularly in abstract topics such as the human digestive system, are often caused by the use of monotonous learning media that do not actively involve students. This research aims to create Truth or Dare learning media integrated with the Team Games Tournament (TGT) model to enhance the learning outcomes of eleventh-grade high school students on the topic of the digestive system. Methodology: This study uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Validation was conducted by subject matter experts and media experts, while practicality and effectiveness were tested through student and teacher response questionnaires, as well as pre- and post-tests. Findings: Validation results indicated that the media was highly valid, with a score of 98% for the subject matter and 82,1% for the media. Teacher and student responses indicated that the media was highly practical, with scores of 95,5% and 90,4%, respectively. The N-Gain analysis showed a high level of effectiveness, with a score of 0,76. This media has proven capable of improving student learning outcomes while fostering active, collaborative, and enjoyable engagement in learning. Thus, the Truth or Dare-based TGT learning media is suitable as an innovative alternative in Biology education to enhance student learning outcomes, particularly for abstract topics such as the human digestive system. Contribution: These results demonstrate the potential contribution of game-based learning in biology education as an alternative to foster student-centered and meaningful learning